IMPLEMENTASI SURAT EDARAN JAKSA AGUNG NOMOR: B-113/F/FD.1/05/2010 DALAM PENYELESAIAN TINDAK PIDANA KORUPSI DENGAN KERUGIAN NEGARA YANG KECIL OLEH KEJAKSAAN TINGGI RIAU. - Arrasid, Sandi Ersya; Deliana, Evi; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corruption is a serious crime, then the effort to eradicate corruption needs to be done seriously, and continuously. Settlement of corruption cases based on the Attorney General's Circular Letter Number B-113 / F / Fd.1 / 05/2010 uses the concept of restorative justice by prioritizing the return of state financial losses in cases of corruption with small losses. The purpose of this research are: first, to find out how to resolve corruption with small losses using the Attorney General Circular Letter Number: B-113 / F / Fd.1 / 05/2010 based on the concept of restorative justice in the Riau High Prosecutor's Office, second, to know the obstacles in the implementation of the Attorney General's Circular Letter.This type of research can be classified in the type of sociological research, namely direct research at or the place under study. This research was conducted at the Riau High Prosecutor's Office, while the population and sample were parties related to the problem examined in this study, the source of the data used were primary data and secondary data, the data collection methods in this study were interviews and library research.From the results of the research problem there are two main things that can be concluded. First, the settlement of corruption with a small state loss based on the Attorney General's Circular Letter. The method of resolution is carried out by the prosecutor by issuing a Notification of the Progress of Investigation A2 (cases cannot be upgraded to an investigation), an Order to Stop an Investigation (SP3), and a P-26 Termination of Prosecution (SKPP) Decree. Second, the obstacles in the application of the Attorney General's Circular Letter Numberboth external and internal obstacles, such as irreversible state losses, non-cooperative perpetrator, legal position of Attorney General's Circular Letter, absence of determination loss limits in Attorney General's Circular Letter, and the prosecutor's bureaucratic structure that is nuanced by the command. The author's suggestion, first, the prosecutor's office should prioritize the concept of restorative justice in handling corruption cases with a small state loss. Second, special legislation is made regarding restorative justice in order to provide legal certainty.Keywords: Corruption Crime – Restorative Justice - Attorney General's CircularLetter